Assessing advertisement impact on consumers’ attitude: young consumers’ perspective - Rahman, Muhammad Sabbir; Kayadibi, Saim; Uddin, ANM Meshquat; Haque, Md. Mahmudul; Highe, Abdul Highe (TextRoad Publication, 2013)
To attract a substantial amount of young consumers’ towards the fast food restaurant in recent time companies in Bangladesh are facing numerous challenges with spending huge amount of the budget every year on advertising to promote their products to influence consumers’ positive attitudes towards their store. Since there is a significant research gap exists in fast food restaurant’s consumers’ particularly Bangladeshi young consumers’ perspective. The goal of this research is to explore the young consumers’ attitude towards fast food restaurant’s advertisement under three types of advertising practices (Print; Electronic and Online). This research used a self-administered questionnaire on a sample of 350 young consumers aged between 14 and 25 years. Data were analyzed using exploratory factor analysis and multiple regressions. The result of the research shows that young consumers’ are significantly influenced by television advertisement. The findings suggested significant implications that will help fast food restaurants’ formulate better advertisements. For instance, managers can change their slogans based on the current situations which will assist them to create suitable advertising for their targeted customers. KEYWORDS: Consumer Attitude, Print Advertising, Television Advertisement, Internet Advertising, Young Consumers, Fast Food Restaurants, Bangladesh, Developing Country, Consumption Behavior.